Pengaruh Pembelajaran Matematika Dengan Metode Problem Solving Terhadap Kemampuan Penyelesaian Soal Cerita Pada Siswa Kelas IX SMP Negeri 6 Batauga - Anwar Anwar; Minarti Rajun (Jurnal Akademik Pendidikan Matematika, 2021)
The formulation of the research problem is whether there is an effect of learning mathematics with problem solving methods on the ability to solve story problems in class IX students of SMP Negeri 6 Batauga?. The purpose of this study was to determine the effect of learning mathematics with problem solving methods on the ability to solve story problems in class IX students of SMP Negeri 6 Batauga. This research is a quantitative research with a quasi-experimental design method. The population in this study were students of class IX SMP Negeri 6 Batauga which consisted of 2 study groups with details of class IX A as many as 23 students and class IX B as many as 22 students and the samples in this study were taken from the entire population. This research data collection by using tests. The research data were analyzed using the average difference test. However, previously, descriptive analysis and inferential analysis were carried out. The results of this study showed that based on the results of descriptive analysis the average value of the increase in test results of experimental class students was 23.7391, the average increase in test results of control class students was 16.4762, and based on the results of inferential analysis by looking at the normality test, a significant value was obtained. the test results of the experimental class students were 0.200 and the control class was 0.133, while the homogeneity test showed a significant value in both classes 0.073 > 0.05. So it can be said that the two classes are normally distributed and homogeneous. By using the t-test, it is known that the significant value is 0.001 <0.05, which means that H0 is rejected. So it was concluded that there was an effect of learning mathematics with problem solving methods on the ability to solve math story problems in class IX students of SMP Negeri 6 Batauga.